What it is to see? - Gil, José; Vásquez Tamayo (Traductor), Carlos (Estudios de Filosofía, 2011)
The present article aims at analyzing the limits and requirements of the poetical view of Alberto Caeiro, pseudonym for Fernando Pessoa. This view, maintains Gil, is singular, it supposes a process of criticism of the traditional subject-object relationship in the act of knowing. A type of epojé in the phenomenological sense of the term. It is not an empirical outlook, nor does it appeal to the senses, it is an outlook which has more the character of “an intellectual intuition of the senses”. The deeper purpose of the article is to show how the paganism advocated by Caeiro appeals to an “absolute objectivism” and claims as it most proper invention a harmonizing of the act of feeling with the act of thinking. Gil´s essay develops his arguments following step by step some of the poems of Caeiro the poet as well as some statements on him by Pessoa himself.